Nikah Subarang Ayie Kontestasi Nikah Formalistik di 50 Kota Sumatera Barat - hanani, silfia; Alfin, Aidil; Rahman, Ali (UIN Sunan Kudus, 2020)
Subarang Ayie marriage, marriages that are performed through marriage services that are not regulated by the state, or not through procedures that have been established by applicable laws and regulations, so that this marriage does not have official documents, as regulated by the state. Ayie's Subarang marriage still occurs due to practices carried out by actors who need and need each other, making it difficult to be eliminated. Marriage under the hand is still a rational and normative choice, especially among those who have problems in marriage. Therefore, Subarang Ayie's marriage still survives.